Modified Radical Mastectomy under Local Anesthesia in High-Risk Male Breast Cancer - Elif Çolak; Ömer Alıcı (European Journal of Breast Health, 2015)

(untitled)
Carcinoma of the male breast is responsible for less than 1% of all malignancies in men, but the prognosis is poor. Being diagnosed at an older age and advanced stage both affect the prognosis. Surgical treatment of elderly patients with co-morbid diseases is challenging. Unfortunately, these patients do not receive chemotherapy due to poor overall status. Mastectomy with local anesthesia may be an option for these patients. We aimed to present an elderly male patient who underwent successful mastectomy and axillary dissection under local anesthesia.